Manajemen Pelatihan Permainan Tradisional Edukatif Berbasis Potensi Lokal Dalam Meningkatkan Pengetahuan Dan Keterampilan Orang Tua Anak Usia Dini - Abdul Rahmat; Mira Mirnawati (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2021)
The results of this study generally concluded (1) study participants do not yet have advanced literacy skills that are meaningful to the needs of life, because the materials learning materials and learning activities do not fit the needs of local tutors, (2) development of literacy learning model based on local potential of agriculture can significantly empower Indigenous Communities. Local potential is developed into a learning module literacy, literacy tutor training, learning implementation, and evaluation of results provided by the potential skills of local content, (3) implementation of the development of functional literacy learning model based on local potential of agriculture is packaged in three stages, namely preparation, implementation, and evaluation (4) the effectiveness of the development model of literacy learning in study groups to apply model-based functional literacy development of local potential is better when compared with the study group who did not apply the intervention model development study. The effectiveness of model development, learning development and empowerment of remote indigenous communities in literacy programs, with one another have a significant positive relationship. The effectiveness of model development and learning development partially or simultaneously both significant positive effect on the empowerment of remote indigenous communities in the functional literacy program.